2001
DOI: 10.1046/j.1523-536x.2001.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women's Perceptions of Their Nurse's Role During Labor and Delivery

Abstract: The expectations of women in our study were in contrast with findings from two previous work sampling studies, in which nurses provided much less time giving women physical comfort, emotional support, and informational support than would have been expected by women in our study. Fulfilling women's expectations about childbirth can increase women's satisfaction with their birth experiences. Further studies can help maternity caregivers learn more about women's expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 12 publications
3
64
1
5
Order By: Relevance
“…The fi nding of others studies indicated that family, friends and internet were woman's primary sources of information about childbirth 19,32 19 . Other study reported that the majority of women perceived midwifery care during childbirth as a good source of information 31 . Childbirth education classes can prepare women for unpleasant aspects of labor and birth.…”
Section: Discussionmentioning
confidence: 99%
“…The fi nding of others studies indicated that family, friends and internet were woman's primary sources of information about childbirth 19,32 19 . Other study reported that the majority of women perceived midwifery care during childbirth as a good source of information 31 . Childbirth education classes can prepare women for unpleasant aspects of labor and birth.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lewis (1990: 15) argues that 'there has always been a gap between the perceptions and demands of women in respect to maternity policies and practices, and what has been offered by policy-makers and professionals'. Tumblin & Simkin (2001) claim that fulfilling women's expectations about childbirth can increase women's satisfaction with their birth experiences. Proctor (1998) underlines the importance of understanding the concerns and needs of women by midwives.…”
Section: Discussionmentioning
confidence: 99%
“…Methodologies were variously described as qualitative (n=4) (Berg et al, 1996;Brown et al, 2009;Dahlen et al, 2010;Walker et al, 1995), using a phenomenological (n=1) (Berg et al, 1996) or Grounded Theory approach (n=3) (Brown et al, 2009;Dahlen et al, 2010;Walker et al, 1995). Two authors utilised quantitative methods (Green et al, 1990;Tumblin & Simkin, 2001). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations